2022
DOI: 10.24018/ejfood.2022.4.3.500
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Organic and Inorganic Fertilizers on Growth, Yield and Nutrient Uptake of Cauliflower in Acidic Soil of Bangladesh

Abstract: Soil acidity is considered as one of the limiting factors in agricultural production because it affects plant growth and development by reducing the availability of essential nutrients. Therefore, a field trial was carried out at the experimental field of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur, Bangladesh from September 2021 to January 2022 to evaluate the effect of various organic and inorganic fertilizers on the growth, yield, and nutritional quality of cauliflower. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Integration of organic manures with inorganic fertilizers also enhance soil properties particularly the soil organic carbon status and microbial community [22][23]. It has been also reported that combined application of manures and inorganic fertilizers increases cauliflower production in acid soil of Bangladesh [24]. Thus, economic and eco-friendly application of manures along with mineral fertilizers for profitable vegetable yield and sustainable soil health is a long-awaited demand both in agriculture and horticulture.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of organic manures with inorganic fertilizers also enhance soil properties particularly the soil organic carbon status and microbial community [22][23]. It has been also reported that combined application of manures and inorganic fertilizers increases cauliflower production in acid soil of Bangladesh [24]. Thus, economic and eco-friendly application of manures along with mineral fertilizers for profitable vegetable yield and sustainable soil health is a long-awaited demand both in agriculture and horticulture.…”
Section: Introductionmentioning
confidence: 99%
“…Manures of both plant and animal sources bear great potential to enhance crop production and sustain soil fertility (Adekiya et al, 2019;Akhtar et al, 2019;Khanam et al, 2022;Salma et al, 2022). Manure reduces the use of inorganic fertilizers in crop production and lessens the detrimental effects on air, water, and soil environment (Iqbal et al, 2020).…”
Section: Improved Manure Managementmentioning
confidence: 99%
“…Nutrient uptake from the soil was calculated by using the formula: Nutrient uptake = (% A x Y) ÷ 100 kg ha -1 [12] Where, %A = Nutrient content of plant dry matter in percent Y = Total dry matter production of plant (kg ha -1 ) Soil moisture used by the crop was determined by using the following formula:…”
Section: Harvesting and Data Collectionmentioning
confidence: 99%